2019
DOI: 10.1371/journal.pone.0215458
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based validation of spatial capture-recapture models: A case study using mountain lions

Abstract: Spatial capture-recapture (SCR) models have improved the ability to estimate densities of rare and elusive animals. However, SCR models have seldom been validated even as model formulations diversify and expand to incorporate new sampling methods and/or additional sources of information on model parameters. Information on the relationship between encounter probabilities, sources of additional information, and the reliability of density estimates, is rare but crucial to assessing reliability of SCR-based estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…This increase in density and abundance result from the non-local model potentially biasing the effective sampling area low because encounter probabilities decline as more traps are included that are outside of an individual's trap detection range. Paterson et al (2019) also noted the potential for biased abundance estimates in SCR models when detection probabilities are lower but in reference to inadequate search effort and correlation between search effort and density. Thus, our result may suggest that future SCR analyses should implement a local evaluation approach, especially if they have large study areas (or trapping grids) relative to animal activity areas.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in density and abundance result from the non-local model potentially biasing the effective sampling area low because encounter probabilities decline as more traps are included that are outside of an individual's trap detection range. Paterson et al (2019) also noted the potential for biased abundance estimates in SCR models when detection probabilities are lower but in reference to inadequate search effort and correlation between search effort and density. Thus, our result may suggest that future SCR analyses should implement a local evaluation approach, especially if they have large study areas (or trapping grids) relative to animal activity areas.…”
Section: Discussionmentioning
confidence: 99%
“…The number of sampling-days, level of search effort, number of samples included in analysis, number of individuals identified, and number of spatial recaptures varied across study areas and time periods (Table 3). The number of individuals identified and the number of spatial captures in each study area and time period, together with previous simulation-based work on the same study design, suggested that each dataset was adequate to result in unbiased spatial-capture recapture abundance estimates (Table 3; Paterson et al 2019a). We radio-collared a total of 15 animals (9 female, 6 male) in the Bitterroot study area and 9 (6 female, 3 male) in the Clark Fork study area.…”
Section: Mountain Lion Harvest Management and Samplingmentioning
confidence: 87%
“…The SCR model component for the distribution of animal activity centers in space included a covariate representing a separately estimated mountain lion resource selection function (RSF; Robinson et al 2015). Previous work suggested this RSF was a strong predictor of activity centers (Proffitt et al 2015, Paterson et al 2019a. The RSF predicted the relative probability of mountain lion use during winter (1 Dec-15 Apr) and was developed based on GPS location data from 85 independent-aged collared male and female mountain lions from 9 different study areas in Montana (Robinson et al 2015).…”
Section: Spatial Capture-recapture Modelingmentioning
confidence: 99%
See 2 more Smart Citations